Leveraging Consumption Intention with Identity Information on Sharing Economy Platforms. Issue 2 (4th March 2019) - Cho, Sunyoung; Park, ChongWoo; Kim, Junghwan
ABSTRACT: Sharing economy platforms enable individuals to collaboratively consume underutilized resources by linking peer-providers and peer-consumers. One interesting observation on sharing economy platforms is unprecedented amount and use of identity information about peer-providers. Peer-providers offer rich information about themselves, and a sub-set of such identity information is verified on some sharing economy platforms. However, there has been little research on such identity information sharing and the impacts of such information on peer-consumers' decision making. In this study, we propose a research model to explain the role of identify information on sharing economy platforms, and empirically test the proposed model in the context of a lodging service sharing economy platform, Airbnb. Our results show that identity information shared by peer-providers contributes to peer-consumers' consumption intention through social presence and trust. The implications of these findings and directions for future research are discussed.